The Normalization of Deviant Organizational Practices: The Non-performing Loans Problem in China - Li, Jiatao; Ng, Carmen K. (2013)
Research on deviant organizational practices has demonstrated that normative and cognitive institutional forces contribute to making deviance acceptable. Data from a survey of 3,751 Chinese firms were applied to test the idea that a clearly articulated alternative identity is necessary if a firm is to resist the normalization of deviance. Widespread acceptance of delinquency in repaying loans was shown to make it more likely that a firm adopts that practice, but this normalization process is less likely for firms with a stronger anti-deviance identity.
Keywords: Payment arrears; Non-performing loans in China; Ethics in management; Deviance; Normalization